The effect of perception training with synthetic and natural stimuli on BP learners' ability to identify the English vowels /æ-? - Rosa, Elisabeth Ann Bunch Oliveira da (2022)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês: Estudos Linguísticos e Literários, Florianópolis, 2022.